1993
DOI: 10.1073/pnas.90.20.9355
|View full text |Cite
|
Sign up to set email alerts
|

Tie-1 and tie-2 define another class of putative receptor tyrosine kinase genes expressed in early embryonic vascular system.

Abstract: We report the molecular cloning and characterization of two structurally related putative receptor tyrosine kinases, encoded by distinct genes (tie-i and tie-2) on mouse chromosome 4. Both tie-i and tie-2 encode receptor proteins possessing unique multiple extracellular domains: two immunoglobulin-like loop domains flanking three epidermal growth factor repeats followed by three fibronectin-type III

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
238
1
5

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(246 citation statements)
references
References 26 publications
2
238
1
5
Order By: Relevance
“…Several studies have suggested that the Tie protein plays an important role in angiogenesis Sato et al, 1993;Korhonen et al, 1994Korhonen et al, , 1995. In recent studies high amounts of Tie mRNA and also Tie protein have been detected in human brain tumours in contrast to the less abundant expression of Tie mRNA or protein in the respective normal brain tissue control samples (Kaipainen et al, 1994;Hatva et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have suggested that the Tie protein plays an important role in angiogenesis Sato et al, 1993;Korhonen et al, 1994Korhonen et al, , 1995. In recent studies high amounts of Tie mRNA and also Tie protein have been detected in human brain tumours in contrast to the less abundant expression of Tie mRNA or protein in the respective normal brain tissue control samples (Kaipainen et al, 1994;Hatva et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Tie and Tek (Dumont et al, 1993) are members of a new subfamily of endothelial cell RTKs whose extracellular domains contain three different types of structural motifs: immunoglobulin (Ig)-like loops, cysteine-rich epidermal growth factor (EGF)-like domains and fibronectin type III (FN III) domains (Maisonpierre et al, 1993;Sato et al, 1993;Ziegler et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to VEGF, the specificity of the Ang for the vascular endothelium results from the restricted distribution of their receptors, Tie1 and Tie2, to these cells. Tie1 and Tie2 are also receptor tyrosine kinases (Sato et al, 1993). All the known Ang bind primarily to Tie2 and it is unclear whether there are independent ligands for the second Tie receptor, Tie1.…”
Section: Angiopoietinsmentioning
confidence: 99%
“…The Tek receptor is ®rst expressed around day 7.5 during mouse development, and it is expressed by endothelial precursors and by the endothelium of actively growing blood vessels (Dumont et al, 1992;Sato et al, 1993). Tek has recently been shown to be expressed at relatively high levels in the quiescent vasculature of a number of adult tissues as well as in healing skin wounds (Wong et al, 1997).…”
Section: Introductionmentioning
confidence: 99%